1994
DOI: 10.1093/carcin/15.5.869
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectra of 1,2-dibromoethane, 1,2-dichloroethane and 1-bromo-2-chloroethane in excision repair proficient and repair deficient strains of Drosophila melanogaster

Abstract: DNA sequence changes produced by 1,2-dibromoethane (DBE), 1,2-dichloroethane (DCE) and 1-bromo-2-chloroethane (BCE) were analyzed using the vermilion locus of Drosophila melanogaster. Under excision repair proficient (exr+) conditions (mutagenized exr+ males mated with exr+ females) all mutants isolated from the first generation (F1) after DBE and DCE exposure represented DNA rearrangements (multi-locus deletions, small deletions with tandem repeats, duplicate insertions). By contrast, mutants expressing a ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…as shown in the upper part of this figure. A repair time course was established for each position, and the time at which 50% of the initial damage was removed was then determined from a semilogarithmic plot (log 10 [adduct] versus t). C, mutations (from Table III).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as shown in the upper part of this figure. A repair time course was established for each position, and the time at which 50% of the initial damage was removed was then determined from a semilogarithmic plot (log 10 [adduct] versus t). C, mutations (from Table III).…”
Section: Discussionmentioning
confidence: 99%
“…Adduct t1 ⁄2 (the time at which 50% of the initial damage was removed was then determined from a semi-logarithmic plot, i.e. log 10 [adduct] versus t) was determined for every damaged G in both strands in exons 5-8.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, we have studied the DNA adducts derived from the episulfonium ion pathway (16,20,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). S-[2-(N 7 -Guanyl)ethyl]GSH is the major adduct (20,26,27) but the N 2 -and O 6 -guanyl adducts (35)(36)(37) may also contribute to explain the predominance of GC:AT transitions in several organisms (35,(38)(39)(40). An unexpected and yet unexplained observation is the increased bacterial mutagenicity seen with expression of O 6 -alkyguanine transferase (41)(42)(43), which does not appear to be related to the GSH conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…A forward mutation assay using bacteriophage M13mp18 with the reactive GSH conjugate S- (2-chloroethyl)GSH revealed that base-pair substitution muta-tions occurred in the lacZ region and GC to AT transitions dominated (7). The same mutational changes were dominant in widely different biological systems such as Drosophila melanogaster, Chinese hamster ovary cells, and Escherichia coli after treatment with EDB (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%